A Rare Association of Posterior Reversible Encephalopathy Syndrome (PRES) with Glomerulonephritis: 2 Case Reports - Afroz, Rafiya; Das, Aditi Rani; Bashar, Fuad Bin; Sarna, Farzana Sultana; Rahim, Abdur; Islam, Mohammad Rafiqul (Journal of Medicine, 2025)
Posterior reversible encephalopathy syndrome (PRES) is a disorder of reversible sub cortical vasogenic brain edema predominantly affecting the posterior occipital and Parietal lobe in the setting of acute changes in blood pressure. PRES is often associated with underlying medical conditions such as hypertension, renal disease, autoimmune disorders, and immunosuppressive therapies. On the other hand, Glomerulonephritis, an inflammatory condition affecting the glomeruli of the kidneys, has been suggested as a potential risk factor for PRES. The mechanism underlying PRES is not certain, but endothelial dysfunction is implicated. Treatment is supportive and involves correcting the underlying cause and managing associated complications, such as seizures. In this case series, we presented two cases of glomerulonephritis with PRES. J MEDICINE 2025; 26: 67-70